From the History of Jews Living in Bukhara Emirate - Khamrayev G’ayrat Ganiyevich (Scientific Trends, 2024)
In this article, some comments were made about the history of the origin, lifestyle and customs of the Jews who immigrated and settled in the territory of the Bukhara Emirate.
Keywords: Jews, Iosif Mamon Maghribi, Moshe Kalontar, N.A. Mayev